Preliminary study of the atmospheric pollen in Ronda (south Spain) - Picornell Rodríguez, Antonio; Recio-Criado, María Marta; Trigo-Pérez, María del Mar; Cabezudo-Artero, Baltasar (De Linares C & Belmonte J, 2017)
Since 1991, the aerobiology research team of the University of Malaga has been sampling and studying the atmospheric pollen content in different localities of Malaga province (SW Spain) (Recio et al. 1998, 2006). Nevertheless, the northwest part of the province had not been studied yet. In order to complete this missing information, a pollen trap was installed in Ronda in December 2016. This locality, the biggest city in the northwest of Malaga province, is located in a rural area close to the natural Parks Sierra de las Nieves and Sierra de Grazalema, surrounded by crops, natural and semi-natural vegetation. The objectives of this preliminary study were to determinate the atmospheric pollen behaviour of the main taxa registered during winter and spring months in Ronda, as well as compare them with the data obtained by Malaga city sampling station during the same period in order to search for significant differences. The samplings were made by means of two Hirst-type volumetric pollen traps (Hirst 1952). One of them was placed on the roof of the Perez de Guzman High School (Ronda) and the other was located on the roof of the Faculty of Sciences building (Malaga). Samples obtained were mounted and counted according to the methodology proposed by the Spanish Aerobiology Network, the REA (Galán et al. 2007). Significant differences (α = 0.05) between Ronda and Malaga were found regarding the daily concentration of pollen. These differences were particularly detected for some pollen types such as Mercurialis, Fraxinus, Urticaceae and Cupressaceae. In general, we found higher pollen concentration levels in Ronda. We can see a delay for some taxa in Ronda. The higher concentrations of pollen detected in Ronda can be justified by the abundant surrounding vegetation. The differences in concentration and seasonal behaviour detected for some taxa can be explained by the different thermotype and ombrothype of the two sampling sites and the natural distribution and abundance of these taxa in the province.
ISBN: 978-84-945378-7-5 (Book) ISBN: 978-84-945378-8-2 (e-Book) Available in http://lap.uab.cat/aerobiologia/es/bibliography#organizedcongresses
Keywords: Botánica; Biología Vegetal; Aerobiology; Pollen; Allergy; Ronda